Synthesising circus aesthetics and science: Australian circus and variety theatre at the turn of the twentieth century. Issue 3 (3rd July 2018) - Arrighi, Gillian
ABSTRACT: With a focus on popular entertainments in Australia at the turn of the twentieth century, this article examines the aesthetic slippage that occurred between the circus and the variety theatre. Utilising the lens of science – or more particularly, popular science – it examines circus-style acts that either promoted recent scientific understanding, or that were received by audiences as evidence of scientifically structured human activity. By the end of the nineteenth century, circus owners defended their display of animals on the basis that they were guardians and promoters of new understanding in the field of natural history. Acts that promoted interest in animal intelligence and interspecies communication are identified as transferring from the circus to the variety theatre in Australia. Performances that reflected interest in human physiology and health sciences are similarly highlighted as originating at the circus and subsequently being sustained at the variety theatre. In the early years of the twentieth century extraordinary displays of human strength, speed and agility were positioned within the field of medical and health science by the owners of variety theatres and circuses. This article explores the ways that circus and the variety theatre mediated science for Australia's popular audiences at the turn of the twentieth century. It contributes new understanding about ways the circus manifested and evolved in different regions at different times and responded to multiple social and industrial influences within its geographic context.